Analysis of Locus of Control and Self Efficacy on Satisfaction Employee Work and its Impact on Performance Achievement Levels - Safitri, Wahyu; Zulher, Zulher; Basem, Zamhir (Sebatik, 2024)
The Kampar Regency Ministry of Religion Office has the primary responsibility of formulating and establishing the vision, mission, and technical policies related to religious life services and community guidance in Kampar Regency. This includes providing services, guidance, and support in the fields of Hajj and Umrah. Therefore, employees with optimal performance are essential. Many factors influence employee performance, including job satisfaction, locus of control, and self-efficacy. This research was conducted at the Ministry of Religion Office in Kampar Regency, located on Jalan DI Panjaitan, Bangkinang District. The aim of this study is to examine and analyze the following: the influence of locus of control on employee job satisfaction; the influence of self-efficacy on employee job satisfaction; the direct effect of locus of control on employee performance; the direct effect of self-efficacy on employee performance; the effect of job satisfaction on employee performance; the indirect influence of locus of control on employee performance through job satisfaction; and the indirect influence of self-efficacy on employee performance through job satisfaction. This study used primary and secondary data obtained through questionnaires, observations, interviews, and research documentation. The population consisted of all 48 employees at the Kampar Regency Ministry of Religion Office, all of whom were included as the sample. Data analysis was conducted using Structural Equation Modeling (SEM) with hypothesis testing performed at a 5% alpha level. The results of this study concluded that locus of control does not have a significant effect on job satisfaction, while self-efficacy has a significant effect on employee job satisfaction. Locus of control has a direct and significant effect on employee performance, and self-efficacy has a direct and significant effect on employee performance. Job satisfaction significantly affects employee performance. Furthermore, locus of control does not have a significant indirect effect on employee performance through job satisfaction, while self-efficacy has a significant indirect effect on employee performance through job satisfaction at the Kampar Regency Ministry of Religion Office.